BUILDING STUDENTS’ CHARACTER THROUGH EXPOSITION TEXTS: A TEXTBOOK ANALYSIS - Prasetya Ningasih, Tuty; Sri Ardiasih, Lidwina; Saehu, Andang (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study identifies how exposition texts in Grade XI English textbooks contribute to character building using the 4C paradigm. Curriculum Merdeka is the guideline for promoting student autonomy and a pedagogical shift towards the 21st-century soft skills framework. This study employed qualitative case study analysis and interviews to evaluate the exposition texts of Ministry of Education-approved textbooks, assessing their capacity to enhance character building in eleventh-grade students. The case study analysis reveals that exposition texts primarily address ethical issues and social concerns, providing several opportunities for character education. However, the associated learning activities demonstrated the consistency of the 4C paradigm, with critical thinking, communication, collaboration, and creativity regularly included in the process of character development during the teaching-learning process. Expository text should be used to improve moral reasoning, perspective-taking abilities, and ethical awareness for eleventh-grade students at school. English textbooks provide students with the selection and use of exposition texts to maximize their contribution to overall character building in secondary education. The implementation of 4C in the activities included in the English textbook enables students to be more aware of their environment in a wise manner.